Nutrient- and Climate-Induced Shifts in the Phenology of Linked Biogeochemical Cycles in a Temperate Estuary - Testa, Jeremy M.; Murphy, Rebecca R.; Brady, Damian C.; Kemp, William M. (Frontiers in Marine Science, 2018)
The response of estuarine ecosystems to long-term changes in external forcing is strongly mediated by interactions between the biogeochemical cycling of carbon, oxygen, and inorganic nutrients. Although long-term changes in estuaries are often assessed at the annual scale, phytoplankton biomass, dissolved oxygen concentrations, and biogeochemical rate processes have strong seasonal cycles at temperate latitudes. Thus, changes in the seasonal timing, or phenology, of these key processes can reveal important features of long-term change and help clarify the nature of coupling between carbon, oxygen, and nutrient cycles. Changes in the phenology of estuarine processes may be difficult to assess, however, because many organisms are mobile and migratory, key primary and secondary producers have relatively rapid physiological turnover rates, sampling in time and space is often limited, and physical processes may dominate variability. To overcome these challenges, we have analyzed a 32-year record (1985-2016) of relatively frequent and consistent measurements of chlorophyll-a, dissolved oxygen, nitrogen, and physical drivers to understand long-term change in Chesapeake Bay. Using a suite of metrics that directly test for altered phenology, we quantified changes in the seasonal timing of key biogeochemical events, which allowed us to illustrate spatially- and seasonally-dependent shifts in the magnitude of linked biogeochemical parameters. Specifically, we found that a modest reduction in nitrate input was linked to a suppression of spring phytoplankton biomass in seaward Bay regions. This was, in turn, associated with an earlier breakup in hypoxia and decline in late-summer NH4+ accumulation in seaward waters. In contrast, we observed an increase in winter phytoplankton biomass in landward regions, which was associated with elevated early summer hypoxic volumes and NH4+ accumulation. Seasonal shifts in oxygen depletion and NH4+ accumulation are consistent with reduced nitrogen inputs, spatial patterns of chlorophyll-a, and increases in temperature. In addition, these increases have likely elevated rates of organic matter degradation, thus “speeding-up” the typical seasonal cycle. The causes for the recent landward shift in phytoplankton biomass and NH4+ accumulation are less clear; however, these altered patterns are analyzed here and discussed in terms of numerous physical, climatic, and biological changes in the estuary.